2012
DOI: 10.1111/pde.12014
|View full text |Cite
|
Sign up to set email alerts
|

Linear Lupus Erythematosus Profundus as an Initial Manifestation of Systemic Lupus Erythematosus in a Child

Abstract: The case of a 13-year-old Caucasian girl with a 1-year history of a linear plaque on her thigh is reported. Histopathologic examination of the incisional biopsy tissue established the diagnosis of lupus erythematosus panniculitis. Six months later she developed the clinical and laboratory criteria for the diagnosis of systemic lupus erythematosus (SLE). She was treated with azathioprine and oral prednisolone, with a favorable clinical outcome. Our case illustrates a child with linear lupus erythematosus profun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…More than 70% of children with SLE have skin lesions, and in one-third they may be the presenting feature (2,3,5). The spectrum of CLE and its relationship to SLE has been well characterized in adults, but the data in children are limited to isolated case reports or small series focusing on one subset of CLE (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). A few reports have included the whole spectrum of CLE in children (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…More than 70% of children with SLE have skin lesions, and in one-third they may be the presenting feature (2,3,5). The spectrum of CLE and its relationship to SLE has been well characterized in adults, but the data in children are limited to isolated case reports or small series focusing on one subset of CLE (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). A few reports have included the whole spectrum of CLE in children (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…The range in severity of lupus profundus varies, with some cases being associated with a relatively benign clinical course , whereas other case reports have reported serious comorbid complications such as vasculitis, peripheral polyneuropathy, and facial nerve paralysis . Up to the time of this report, no systemic involvement had been detected in our patient.…”
Section: Discussionmentioning
confidence: 55%
“…Usually cutaneous lesions following the lines of Blaschko reflect the most common form of mosaic condition to derive from a post‐zygotic somatic mutation in hamartomas and pigmentary or inflammatory monogenic disorders . However, in inflammatory multifactorial polygenic diseases (like lichen, psoriasis, or lupus), segmentary lesions following Blaschko's lines can also occur and are considered as isolated segmentary lesions that may coexist with non‐segmental lesions later in life . These cases may be explained by an early post‐zygotic event in the form of loss of heterozygosity involving one of the genes that predispose to the disorder (“superimposed segmental manifestation”) .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] However, in inflammatory multifactorial polygenic diseases (like lichen, psoriasis, or lupus), segmentary lesions following Blaschko's lines can also occur and are considered as isolated segmentary lesions that may coexist with nonsegmental lesions later in life. 7,8 These cases may be explained by an early post-zygotic event in the form of loss of heterozygosity involving one of the genes that predispose to the disorder (superimposed segmental manifestation). 9 Seitz et al 10 suggested that a linear variant of cutaneous lupus erythematosus can be explained by the presence of genetically variant keratinocytes that lack a protective factor against ultraviolet-induced damage and show aberrant cytokine expression or major histocompatibility complex expression.…”
Section: Discussionmentioning
confidence: 99%